Effect Of Dry Needling Therapy with IASTM on Spasticity in Neurological Conditions - Malvi, Ruchit; Lohar, Deepak; Khan, Jafar; Balala, Deepika; Menria, Shubham; Pinjara, Farukh Mohammad; Pal, Renuka; Kania, Vaishnavi; Jain, Preksha; Bhatanagar, Suhani (Journal of Neonatal Surgery, 2025)
Background: The purpose of this study is to evaluate how well dry needling therapy with IASTM affects spasticity in neurological disorders. It is predicted that using IASTM and dry needling will greatly lessen pain and spasticity and help those who are impacted have more toned muscles. Methodology: A 12-month experimental study was carried on total of 60 neurological patients (≥40 years old) who had spasticity in neurological disorders had IASTM and dry needling therapy three times a week for 45 minutes each session for 2.5 months. VAS and MAS were used to measure pain and spasticity. Results: Participants' muscle tone improved statistically significantly (p < 0.05) between pre- and post-intervention ratings, according to paired t-test analysis. A statistically significant improvement (p < 0.05) was observed in both spasticity and pain levels when comparing pre-test and post-test results among participants. Conclusion: By enhancing proprioception and muscular relaxation, dry needling and IASTM assist neurological patients experience less spasticity